FAKTOR EKSPLOITASI DAN KUANTIFIKASI LIMBAH KAYU DALAM RANGKA PENINGKATAN EFISIENSI PEMANENAN HUTAN ALAM - Matangaran, Juang Rata (Bumi Lestari Journal of Environment; Vol 13 No 2 (2013), 2013)
Abstract The objectives of the research were to find out the exploitation factor and quantify of logging residue from forest harvesting operation. Logging residue is defined as stump, trimming from stem, trimming from upper stem and branches which has 30 cm as minimum diameter and 4 meter of minimum length. Data was collected from two forest company, in Central Kalimantan and West Sumatera. Data were measured at 10 sample plots in each 1 hectare at those both location. Result of the study showed that logging residue occurred at the harvested site, landing site and at the logyard. Logging residue in each hectare at Central Kalimantan more than West Sumatera but in each tree quantity of logging residue was nearly same at both location.The percentage of logging residue at Central Kalimantan was 33,8%, and at the West Sumatera was 30,4 %. Exploitation factor of logging operation was 0,75 at West Sumatera and 0,74 at Central Kalimantan. This number indicated that the recovery rate of forest harvesting operation was about 75 % at those both forest companies.
Keywords: Keyword: exploitation factor, recovery rate, logging residue, forest harvesting.